ATIVIDADE METANOGÊNICA ESPECIFICA DA CODIGESTÃO ANAERÓBIA DE DEJETOS DE OVINOS E SUÍNOS - LECCIOLLI, Renan Barbosa; GONÇALVES, Isabela Pinto; SANTOS, Tânia Mara Baptista Dos; CORREA, Jonas de Sousa (ANAIS DO ENIC, 2020)
-